Patient and Procedural Factors that Influence Anesthetized, Nonoperative Time in Spine Surgery. (August 2016) - Puffer, Ross C.; Mallory, Grant W.; Burrows, Anthony M.; Curry, Timothy B.; Clarke, Michelle J.
Study Design: Retrospective study. Objective: Efficient use of operating room time is important, as delays during induction or recovery increase time not spent operating while in the operating room. We identified factors that increase anesthetized, nonoperative time by utilizing a database of over 5, 000 consecutive neurosurgical spine cases. Methods: Surgical records were searched to identify all spine surgeries performed between January 2010 and July 2012. Anesthetized, nonoperative time was calculated from the anesthesia record and compared with both patient and procedure characteristics to determine any significant relationships Results: There were 5, 515 surgical cases with a mean age of 60.5 and mean body mass index (BMI) of 29.7; 3, 226 (58%) were male subjects. There were 1, 176 (21%) fusion cases, and level of pathology was predominantly lumbar (4, 010 cases, 73%). Fusion cases had a significantly longer total anesthetized, nonoperative time (fusion: 98 minutes, nonfusion: 76 minutes, mean difference: 22 minutes, p  < 0.0001). Significant factors affecting anesthetized, nonoperative time in nonfusion cases include age greater than 65 years (mean difference 5 minutes, p  < 0.0001), American Society of Anesthesiologists (ASA) grade, and BMI (BMI < 25: 72 ± 1.2 minutes, BMI 25 to 29: 74 ± 0.6 minutes, BMI 30 to 39: 79 ± 0.6 minutes, BMI 40 + : 87 ± 1.8 minutes, p  < 0.0001). Similarly, for fusion operations, age > 65 years significantly increased nonoperative time (mean difference 6 minutes, p  < 0.01), as did increasing ASA (mean difference 9 minutes, p  < 0.0001) and increasing BMI. Conclusion: Patient and surgical factors, including ASA grade, BMI, level of pathology, and surgical approach, have noticeable effects on anesthetized, nonoperative times in spine surgery.